1992
DOI: 10.1093/geronj/47.5.s233
|View full text |Cite
|
Sign up to set email alerts
|

Are Older People Most Afraid of Crime? Reconsidering Age Differences in Fear of Victimization

Abstract: The reasons why previous studies of fear of crime yield different conclusions regarding age differences are examined. Data from a national survey of adults are used to assess whether older adults manifest the highest levels of fear of crime. No significant relationship was found between age and the commonly used indicators of fear of crime in many previous studies when controlling for relevant factors. Using an alternative strategy for measuring fear of crime--based upon rating fear for 10 different victimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
2
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 0 publications
2
65
2
1
Order By: Relevance
“…Females felt less in control than males and judged the consequences to be higher; they judged likelihood to be higher and felt that their own social group was more likely to fall victim than other social groups. This study also found that younger people worried more frequently than older people about personal crime (but not about property crime) -a finding consistent with the studies of Akers, La Greca, Sellers, and Cochran (1987), Chadee and Ditton (2003), Ferraro and LaGrange (1992), LaGrange and Ferraro (1989) and Ziegler and Mitchell (2003) -but contrary to gender, these differences could not be explained by differential vulnerability or likelihoodperception. And further investigation -which differentiated between personal and property crime -showed that females worried more frequently than males about personal crime, but that there was no gender difference in worry about property crime.…”
Section: Discussionsupporting
confidence: 88%
“…Females felt less in control than males and judged the consequences to be higher; they judged likelihood to be higher and felt that their own social group was more likely to fall victim than other social groups. This study also found that younger people worried more frequently than older people about personal crime (but not about property crime) -a finding consistent with the studies of Akers, La Greca, Sellers, and Cochran (1987), Chadee and Ditton (2003), Ferraro and LaGrange (1992), LaGrange and Ferraro (1989) and Ziegler and Mitchell (2003) -but contrary to gender, these differences could not be explained by differential vulnerability or likelihoodperception. And further investigation -which differentiated between personal and property crime -showed that females worried more frequently than males about personal crime, but that there was no gender difference in worry about property crime.…”
Section: Discussionsupporting
confidence: 88%
“…Older adults do, however, provide larger rewards to people who have invested in them, reflecting a heightened trustworthiness. Studies have also shown that older adults are actually less afraid of being victimized, despite their greater vulnerability to many kinds of crime (32).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with Seccombe and Ishii-Kuntz's (1991) finding that for all cohorts age 55 or older, fear of crime was the most serious problem. Many studies have found that fear of crime is a serious stressor for older adults; however, the actual crime rate is less for older persons than for younger persons (see Ferraro & LaGrange, 1992, for a review). This "victimization/fear paradox" (Ferraro & LaGrange, 1992) emphasizes the traumatic impact of crime on older adults and may explain our result.…”
Section: Discussionmentioning
confidence: 99%